THE ROLE OF THE PASAI SAMUDRA KINGDOM COMPLEX TOURISM OBJECT TOWARDS INCREASING TRADERS' INCOME - Syaputri, Rahmi; Safrina, Lia; Malahayatie (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
The tourism sector is currently one of the sectors that has great potential to increase regional income in Indonesia. However, there are still many areas with tourism potential that are not developed and even tend to be neglected. This is certainly not in accordance with one of the regional government's plans for developing tourist villages. and also the Cultural and Tourism Development Policy instructed by the President Number 16 of 2005. The Samudra Pasai royal complex tourist attraction is located in two locations, namely in Gampong Beuringen and in Gampong Kuta Kareng which is one of the mainstay religious tourist attractions in North Aceh district. This research is qualitative research using descriptive analysis to explain the role of tourist attractions in increasing the income of traders in the surrounding area. Data collection was carried out by interviewing informants from the North Aceh Culture Service, the Samudra Pasai Kingdom Tourism Object Manager, Village Heads and traders. This research provides results that the Samudra Pasai Royal Complex tourist attraction has not provided a maximum role in increasing traders' income.